2014
DOI: 10.1016/j.najef.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Public and private sector jobs, unreported income and consumption gap in India: Evidence from micro-data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…It becomes negative at the top percentiles. By comparison, Azam and Prakash (2015) found this to be positive for the entire wage distribution in India, but still smaller at the top quantiles, while Saha, Roy and Kar (2014) found the premium to be positive at the 25 th quantile and negative at the 50 th and 75 th quantiles. Christofides and Michael (2013), found that the wage gap is negatively related to income quantiles.…”
Section: Estimating the Wage Gap At Various Percentilesmentioning
confidence: 84%
“…It becomes negative at the top percentiles. By comparison, Azam and Prakash (2015) found this to be positive for the entire wage distribution in India, but still smaller at the top quantiles, while Saha, Roy and Kar (2014) found the premium to be positive at the 25 th quantile and negative at the 50 th and 75 th quantiles. Christofides and Michael (2013), found that the wage gap is negatively related to income quantiles.…”
Section: Estimating the Wage Gap At Various Percentilesmentioning
confidence: 84%
“…Therefore, it is interesting to study, as extensions of our model, how our results may change if one revisits our model in the context of developing countries. One such extension can be to allow for rural–urban migration and urban unemployment as in Marjit, Kar, and Hazari () and Saha, Roy, and Kar (). This may be very timely regarding the Chinese engagement in retaliatory tariffs against the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Informal incomes contributes consumption of continuous goods and services. One of the main point in that case in the difference of wages between private and public sector (Saha et al 2014). Strategies of companies are important due to the role of production and eventual risks.…”
Section: Discussionmentioning
confidence: 99%